Experimental and numerical investigation of clinched joint and implementation of the results to design of a tumble dryer - Bayraktar, Meral; Cerkez, Volkan (SPRINGER HEIDELBERG, 2020)
The present paper deals with the numerical modeling and experimental testing of the clinched joint formed by DX51D + AZ150 and AISI 430 material pairs. The strength of the joint was determined experimentally by the tension and shear tests. The numerical model developed for the analysis was successfully validated with the experimental data. The strength of the joint formed by alternative material pairs such as H340LAD + AZ150 and DX52D + Z275 is investigated numerically. The clinched joints between the tumble endplates and flange bodies were done according to the main findings from the previous steps. The study focuses on the strength of the clinched joint as an alternative to flange connection in the case of using different tumble endplate materials. It is concluded that the clinched joint formed by AISI 430 tumble endplate has the highest strength. In the need for tumble capacity increase without changing the design, it is recommended to use AISI 430 material for tumble endplate and to consider strength values of AISI 430 material for capacity control. On the other hand, in case of using three different tumble endplates for the same die, punch and process conditions, the tumble capacity should be evaluated by considering DX52D + Z275 material which has the lowest strength.
Keywords: Clinching process; Finite element method (FEM); Joint strength; Shear strength; Tensile strength; FINITE-ELEMENT-ANALYSIS; MECHANICAL-PROPERTIES; FORMING MECHANISM; STRENGTH; ALUMINUM; BEHAVIOR; Engineering